Use of a Silicon Stoma Stent as an Interim Step in High-Risk Tracheostomy Decannulation. Issue 1 (March 2019) - Ross, Jacqueline; McMurray, Kristy; Cameron, Tanis; Lanteri, Celia
Objective: To describe use of a stoma stent to facilitate high-risk decannulation. Methods: Retrospective chart review of 14 consecutive patients who received a stent from March 2013 to December 2016 at a quaternary health care service. Primary outcome measures were decannulation outcome and adverse events. Results: Decannulation outcome: 12 of 14 patients had their tracheostomy tube (TT) removal facilitated by stent use. Patients had the stent for a median of 6 days (interquartile range, 49). Reasons for use included medical instability, risk of sputum retention, uncertain airway patency, and the need for ongoing airway access. All patients survived to discharge. One patient residing in the community has retained a stoma stent. Adverse events: One patient removed the stent on the day of insertion, necessitating reinsertion of the TT. Granulation tissue at the stoma site was seen in 2 patients. Discussion: A tracheostoma will normally close within 48 hours following decannulation, which is problematic if TT reinsertion is required. By using the stent, reversal of decannulation becomes a simple ward-based procedure. In comparison to a TT, which is secured with ties, the stoma stent proved unsuitable for use in an agitated patient. Implications for Practice: Decreasing total cannulation time is of benefit as patients with tracheostomy are subject to high rates of complications and adverse events. A stoma stent poses little risk and a low morbidity burden to the patient in comparison to alternative management.